CREATIVE TECHNOLOGY AS SOCIAL INFRASTRUCTURE: ENTREPRENEURIAL MODELS FOR SUSTAINABLE DEVELOPMENT - Ingrid Panjaitan; Kunto Adi Rumekso; Muhammad Syukri; Yusak Prakoso; Meera Gupta (Journal of Social Entrepreneurship and Creative Technology, 2026)
Creative technology has emerged as a transformative element in social infrastructure, offering innovative pathways to enhance community engagement, inclusivity, and sustainable development. Traditional social entrepreneurship models often face limitations in scalability, accessibility, and equitable participation, highlighting the need for integrated technological frameworks that support systemic impact. Digital platforms, collaborative tools, and virtual innovation provide mechanisms to facilitate co-creation, resource mobilization, and participatory decision-making within entrepreneurial initiatives. This study aims to examine how creative technology functions as social infrastructure to enable sustainable and inclusive entrepreneurial models. Specific objectives include identifying mechanisms through which technology enhances community engagement, evaluating its impact on measurable social outcomes, and developing a conceptual framework to guide practitioners in designing effective interventions. A mixed-methods approach was employed, combining quantitative surveys of 60 participants with qualitative interviews and case study observations. Data analysis incorporated descriptive and inferential statistics alongside thematic coding to explore patterns of engagement, skill development, and social impact. Findings indicate that technology-mediated social infrastructure significantly increases engagement, co-creation, and empowerment. Structured virtual platforms support role differentiation and iterative learning, fostering sustainable outcomes and social cohesion. The study provides empirical and conceptual evidence that creative technology is a critical enabler of inclusive and scalable social entrepreneurship.